Use of alternative media and different types of recipients in a laboratory culture of Ankistrodesmus gracilis (Reinsch) Korshikov (Chlorophyceae) - doi: 10.4025/actascibiolsci.v33i3.8046 (Acta Scientiarum. Biological Sciences, 2011)
A laboratory culture of Ankistrodesmus gracilis algae was evaluated by studying the biology of the species and its chemical composition in a traditional medium (CHU12) and in two alternative culture media, NPK (20-5-20) and macrophyte (Eichhornia crassipes) + NPK, in three different types of recipients (fiberglass, carboy and plastic bag). First peak in the growth curve of Ankistrodesmus gracilis occurred on the ninth day in macrophyte + NPK medium (74.16 x 105 cells mL-1) in a fiberglass recipient. However, highest density (p < 0.01) was reported in medium CHU12 (122.87 x 105 cells mL-1) in a plastic bag on the twelfth day. Cell density was over 70 x 105 cells mL-1 starting on the twelfth day. Growth rate of A. gracilis was similar (p > 0.05) in culture media in the three recipients. Protein and fiber were similar (p > 0.05) in the treatments, but lipids were higher (p < 0.05) in NPK. Nitrate, ammonia, total phosphorus and orthophosphate contents were over 1 mg L-1 in NPK (p < 0.01). Results show that alternative media, such as NPK and macrophyte + NPK, are possible for large-scale culture of A. gracilis cultured in three types of recipients. Costs are low, occupying less space when cultured in plastic bags and in the laboratory.